123k views
3 votes
Which quadratic equation is equivalent to (x - 4)2 – ( - 4) - 6 = 0?

(u - 4)2 – (u - 4) - 6 = 0 where u = (x - 4)
O v2-(u - 4) - 6 = 0 where u = (x - 4)
O 02 - 16 - 4-6 = 0 where u = (x - 4)
O 02-4-6 = 0 where u = (x - 4)

User Loathian
by
6.0k points

2 Answers

5 votes

Answer:D

Explanation:

User Anpan
by
6.0k points
5 votes

Answer:


u^2-u-6=0

where


u=(x-4)

Explanation:

we have


(x-4)^2-(x-4)-6=0

Let


u=(x-4)

substitute in the expression above


(u)^2-(u)-6=0

Solve for u

Complete the square


(u^2-u+0.25)=6+0.25


(u^2-u+0.25)=6.25

Rewrite as perfect squares


(u-0.5)^2=6.25

square root booth sides


u-0.5=\pm2.5


u=0.5\pm2.5


u_1=0.5+2.5=3


u_2=0.5-2.5=-2

Solve for x

Remember that


u=(x-4)

For u=3


3=(x-4) ---->
x=7

For u=-2


-2=(x-4) ---->
x=2

User Marty Wallace
by
6.1k points